Resveratrol Exacerbates Both Autoimmune and Viral Models of Multiple Sclerosis - Sato, Fumitaka (American Society for Investigative Pathology, 2013)
The polyphenol compound resveratrol is reported to have multiple functions, including neuroprotection, and no major adverse effects have been reported. Although the neuroprotective effects have been associated with sirtuin 1 activation by resveratrol, the mechanisms by which resveratrol exerts such functions are a matter of controversy. We examined whether resveratrol can be neuroprotective in two models of multiple sclerosis: experimental autoimmune encephalomyelitis (EAE) and Theiler’s murine encephalomyelitis virus-induced demyelinating disease (TMEV-IDD). EAE was induced in C57BL/6 mice, which were fed a control diet or a diet containing resveratrol during either the induction or effector phase or through the whole course of EAE. SJL/J mice were infected with TMEV and fed a control diet or a diet containing resveratrol during the chronic phase of TMEV-IDD. In EAE, all groups of mice treated with resveratrol had more severe clinical signs than the control group. In particular, resveratrol treatment during the induction phase resulted in the most severe EAE, both clinically and histologically. Similarly, in the viral model, the mice treated with resveratrol developed significantly more severe TMEV-IDD than the control group. Thus, surprisingly, the resveratrol treatment significantly exacerbated demyelination and inflammation without neuroprotection in the central nervous system in both models. Our findings indicate that caution should be exercised in potential therapeutic applications of resveratrol in human inflammatory demyelinating diseases, including multiple sclerosis.